Indigenous Arbuscular mycorrhizal fungi and growth of tissue-cultured banana plantlets under nursery and field conditions in Rwanda - Jefwa, J.M.; Rurangwa, E.; Gaidashova, S.V.; Kavoo, A.M.; Mwashasha, M.; Robinson, J.; Blomme, Guy; Vanlauwe, Bernard (CAB International, 2013)
Arbuscular mycorrhizal fungi (AMF) have been , .. ridel), evaluated for their suitability in the acclimatization and nursery management of tissue-cultured (TC) plantlets of banana and plantain Improved growth and vigour of plantlets has been documented with exotic AMP species. A wide range of AMF species are associated with banana and plantain (Musa spp.) systems. In this studj~ the use of indigenous AMF from banana and plantain systems was evaluated for nursery management of TC plantlets. ASingle species inoculum with Glomus nwsseae was compared with two mixed inoculants, all derived from banana and plantain systems; these were evaluated on the cultivars 'Mpologoma' (AAA-EA) and 'Kamaramasenge' (AAB) established in two soil types, one with a low P concentration (16-22 mg/kg) and another with high P (50-80 mg/kg). Inoculation with A1-lF enhanced height and leaf surface area growth of Ie plantlets in both soils and both cu1tivars. The inoculation was more effective on 'Mpologoma' than on '](amaramasenge', and mixed inoculants were more effective than the Single-species inoculum, particularly under field conditions, where up to 30'% increase in height, girth and leaf surface area was recorded in 'Mpologoma'. The mixed AMF inoculant comprising species from the soil with low P availability (AMF Kibungo) was most effective in soils with a P concentration of 50-80 mg/kg. High yield was evident in inoculated plants, with a slightly over 30% yield increase for 'Mpologoma' and 'Kamaramasenge' at both the Rubona and Kibungo sites.